Managing neonatal severe sepsis in Germany: a preliminary survey of current practices - Koch, Lutz; Bosk, A.; Sasse, M.; Ruef, P.; Pöschl, Johannes (Klinische Pädiatrie, 2015)
In 2002 and 2007, the American College of Critical Care Medicine (ACCCM) provided clinical guidelines for hemodynamic support of pediatric and neonatal patients in septic shock. In 2008 and 2013, the Surviving Sepsis Campaign (SSC) Guidelines Committee offered up-to-date clinical guidelines for the management of severe sepsis and septic shock in adults and in pediatric patients. The aim of this study was to assess the standard of care of neonates with severe sepsis and septic shock in German neonatal intensive care units (NICUs) with regard to variability in management and guideline conformity.
Gesehen am 14.07.2020